Kebebasan Bersuara: Menimbang Risiko dan Ruang Aman di Era Digital - Dian Rosita; Amirah Dwi Subarkah; Muthmainnah Barakatun Khoomsiati; Prasasti Nugrahaning Gusti; Afifah Salsabila (Lembaga Pengembangan Kinerja Dosen, 2025)
Freedom of expression is a fundamental human right, yet it is not absolute, as it may be restricted under certain conditions in accordance with international law, such as the protection of reputation, national security, and public order. In Indonesia, this right is guaranteed by the 1945 Constitution of the Republic of Indonesia and its derivative regulations. However, the rapid development of information and communication technology has reshaped the landscape of public discourse. The digital space, while facilitating easier access to and dissemination of information, also presents challenges, including hate speech, misinformation, cyberbullying, and the potential for criminalization due to ambiguous regulations.To respond to these challenges, the Regional Board of Nasyiatul Aisyiyah (PDNA) Semarang organized a community service program in the form of a public dialogue titled “Freedom of Speech: Between Rights and Risks” on August 9, 2025, at the Hall of the Central Java Provincial Archives and Library Service. This activity was carried out through a participatory approach by academics who are also members of PDNA, together with the PDNA Semarang board. Two speakers were presented, Dr. Mochamad Riyanto, S.H., M.Si., a legal expert from Universitas 17 Agustus (Untag) Semarang, and Aris Mulyawan, Chair of the Alliance of Independent Journalists (AJI) Semarang. The dialogue produced three main findings: first, the need for legal awareness so that freedom of expression does not lead individuals into legal problems; second, the importance of digital literacy to reduce the spread of hoaxes and hate speech; and third, the urgency of building safe digital spaces through collaboration among communities, media, and educational institutions. The discussion emphasizes that freedom of expression in the digital era must be understood as both a right and a responsibility, requiring a fair regulatory ecosystem and continuous digital literacy enhancement